NOTION PLATFORM AS A TOOL FOR ORGANIZING A DIGITAL EDUCATIONAL ENVIRONMENT - Titova Любов (Journal of Information Technologies in Education (ITE), 2025)
The article explores the possibilities of using the Notion platform to organize the educational process in the context of digital transformation. It is noted that the transition to distance and blended learning requires new approaches to managing learning resources, communication between participants in the educational process, and monitoring learning outcomes. In this context, the Notion platform is seen as a universal tool for creating and organizing a digital learning environment, collaborating, and managing learning projects. The main focus is on the platform’s functionality, which includes tools for creating databases, interactive tables, visual diagrams, and notes that help improve the organization of the educational environment. The platform offers a user-friendly interface adapted for the work of both individual users and groups, which allows organizing the educational process within a single space. Notion provides support for planning learning activities, creating and posting learning materials, project management, task control, and creating documents for collaborative processing, which helps to increase the efficiency of students and teachers. The article emphasizes that Notion allows you to create personalized workspaces, plan group projects, track the progress of tasks, and integrate various types of content, including text, tables, videos, and graphics. The ability to adapt the structure of the platform to the specific needs of users helps to increase the efficiency of work in the educational environment. It is noted that the tool supports the creation of Kanban boards, calendars, schedules, and interactive task lists, which helps structure the process of collaborating on a single document or training project and ensures transparency of task performance. Integration with other services, such as Google Drive, Google Calendar, Zoom, Slack, etc., allows you to create a single educational space that ensures close interaction and collaboration.